1983
DOI: 10.1113/jphysiol.1983.sp014666
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and mechanical activity recorded from rabbit urinary bladder in response to nerve stimulation.

Abstract: SUMMARY1. Responses ofthe smooth muscle membrane ofthe rabbit bladder to intramuscular nerve stimulation were investigated by the micro-electrode and double sucrose-gap methods.2. The cell generated regular spontaneous action potentials. Acetylcholine produced a maintained increase in the frequency and ATP a transient increase. Noradrenaline only increased the frequency at very high concentrations.3. Application of short current pulses (50/isec) produced an initial excitatory junction potential (e.j.p.) with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 20 publications
7
78
0
Order By: Relevance
“…This is in general agreement with previous studies of guinea-pig bladder (De Sy, 1971;Moss & Burnstock, 1985), rabbit and pig bladder (Sibley, 1984) in which atropine resistance has been observed at stimulation frequencies < 10 Hz. Creed et al (1983) have also noted that the late atropine-sensitive component of the electrical response of rabbit bladder to nerve stimulation increased in amplitude and duration with higher frequencies of stimulation. Kasakov & Burnstock (1983) showed that a,fi-methylene ATP abolished the contractile response at stimulation frequencies > 2-4Hz.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is in general agreement with previous studies of guinea-pig bladder (De Sy, 1971;Moss & Burnstock, 1985), rabbit and pig bladder (Sibley, 1984) in which atropine resistance has been observed at stimulation frequencies < 10 Hz. Creed et al (1983) have also noted that the late atropine-sensitive component of the electrical response of rabbit bladder to nerve stimulation increased in amplitude and duration with higher frequencies of stimulation. Kasakov & Burnstock (1983) showed that a,fi-methylene ATP abolished the contractile response at stimulation frequencies > 2-4Hz.…”
Section: Discussionmentioning
confidence: 95%
“…ATP has also been shown to be stored in guinea-pig bladder, although it is not known whether it is co-located with acetylcholine in cholinergic nerves, or is in separate purinergic nerves (Burnstock, 1983). Creed et al (1983) have recorded the electrical responses of rabbit bladder smooth muscle to single stimuli of the intrinsic nerves, and have observed an initial electrical response consisting of an excitatory junction potential (ej.p.) giving rise to a spike, and a delayed more prolonged depolarization of 250-300ms latency and 2s duration.…”
Section: Introductionmentioning
confidence: 99%
“…Early experiments recording electrical activity with the sucrose-gap technique (Creed et al, 1983;Fujii, 1988) pre-supposes that electrical current flows between cells. Furthermore direct measurement of the cable properties of detrusor demonstrated a space constant of more than 1 mm (Seki et al, 1992;.…”
Section: Figure 4 Near Herementioning
confidence: 99%
“…K ϩ efflux through large-conductance Ca 2ϩ -activated K ϩ (BK) channels and voltage-gated K ϩ (K V ) channels is responsible for the repolarization phase of the action potential (29,63). K V channels contribute to the afterhyperpolarization phase along with small-conductance Ca 2ϩ -activated K ϩ (SK) channels (12,21,25). Because BK and SK channels play such a central role in mediating action potential repolarization, blocking them with toxins such as iberiotoxin (IbTX) or apamin, respectively, potentiates the detrusor smooth muscle action potential and greatly increases the force of the resulting contractions (32,44,69).…”
mentioning
confidence: 99%